Selenium Biofortification Modulates Plant Growth, Microelement and Heavy Metal Concentrations, Selenium Uptake, and Accumulation in Black-Grained Wheat - Liu, Yuxiu; Huang, Shuhua; Jiang, Zonghao; Wang, Yizhao; Zhang, Zhengmao (Frontiers in Plant Science, 2021)
In Se-deficient populations, Selenium- (Se-) enriched wheat is a source of Se supplementation, and Se content can be improved by agronomic biofortification. Thus, black-grained wheat (BGW) and white-grained wheat (WGW) (as the control) were grown in Se naturally contained soils at different concentrations (11.02, 2.21, 2.02, and 0.20 mg·kg−1). Then, a field experiment was conducted to assess agronomic performance, the concentration of microelements and heavy metals, and the uptake and distribution of Se in the BGW under the application of Se ore powder. The results showed that the grain yield and grain Se concentration of wheat respectively show a significant increase and decrease from high Se to low Se areas. Higher grain yield and crude protein content were observed in Se-rich areas. The soil application of Se ore powder increased wheat grain yield and its components (biomass, harvest index, grain number, and 1,000 kernels weight). The concentrations of Zn, Fe, Mn, total Se, and organic Se in the grains of wheat were also increased, but Cu concentration was decreased. The concentrations of Pb, As, Hg, and Cr in wheat grains were below the China food regulation limits following the soil application of Se ore powder. Compared with the control, Se ore powder treatment increased the uptake of Se in various parts of wheat plants. More Se accumulation was observed in roots following Se ore powder application, with a smaller amount in grains. In addition, compared with the control, BGW had significantly higher concentrations of Zn, Fe, and Mn and accumulated more Se in grains and shoots and less Se in roots. The results indicate that wheat grown in Se-rich areas increases its grain yield and crude protein content. The soil application of Se ore powder promotes wheat growth and grain yield. Compared with WGW, BGW accumulated more Se in grains and had a higher concentration of organic Se in grains. In conclusion, the application of Se ore powder from Ziyang as Se-enriched fertilizer could be a promising strategy for Se biofortification in the case of wheat, and BGW is the most Se-rich potential genotype.